Britishness Outsourced: State Conduits, Brokers and the British Citizenship Test. Issue 1 (1st January 2022) - Tuckett, Anna
ABSTRACT: This article explores the role of two different types of organisations which act as brokers on behalf of the British state in the citizenship test process. Situating these organisations' emergence within a neoliberal British state characterised by its 'dispersal', it shows that contemporary configurations of the state, market and third sector mean that new and sometimes unexpected actors take on state-like roles. The ambiguous position of these different organisations means that while the reach of the neoliberal state is more diffuse and opaque than ever, clear boundaries between state and non-state realms do continue to exist. Paradoxically, therefore, the blurring of boundaries which characterises the neoliberal state is also accompanied by the hardening of borders between state and non-state realms. This reinforcement of boundaries can appear both to increase state power and to challenge it.